The Anthropology of Cultural Performance - Lewis, L. author. aut Link
XII, 189 p.
Keywords: Contemporary life in most nation-states is not truly cultural, but rather "culture-like," especially in large-scale societies. Beginning with a distinction between special events and everyday life, Lewis examines fundamental events including play, ritual, work, and carnival and connects personal embodied habits and large-scale cultural practices.